Accelerating Equality in Food, Land and Water Systems: Book of Abstracts - CGIAR Gender Equality and Inclusion (International Livestock Research Institute, 2025)
Book of Abstracts for the CGIAR Gender Equality and Inclusion 2025 International Conference held in Cape Town, South Africa, on 7-9 October 2025.